PENGARUH MODEL PEMBELAJARAN CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION) TERHADAP KEMAMPUAN LITERASI SISWA KELAS V SDN 10 PEMULUTAN SELATAN - Viona Novita; Lian, Bukman; Sonia Anisah Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to find out whether the CIRC Learning Model can affect the literacy ability of grade V students of SDN 10 Pemulutan Selatan. The variables used the independent variable (x) in the form of the CIRC learning model and the bound variable (Y) in the form of students' literacy skills. This research is a type of quantitative research using a research method in the form of True Experimental Design with the type of Posttest Only Control Group Design. The sample used was all students of class V with a sampling technique in the form of a saturated sampling while the population used was class VA as an experimental class with 20 students and class VB as a control class with 14 students. The experimental class will be treated using the CIRC learning model while the control class will use the conventional learning model. The data collection techniques of observation, test, and documentation. The normality test analysis uses the Shapiro Wilk, while the hypothesis test uses the T-Test formula. The results of the calculation obtained a ttable value of 2.037 and it was stated that the Tcount > Ttable or 2.967 > 2.037 with a degree of freedom of 32. So based on this statement, it can be concluded that it is significant where Ho is rejected, while Ha is accepted, which means that there is an influence of the use of the CIRC learning model on the literacy ability of grade V students of SDN 10 Pemulutan Selatan.